Sprężysta płyta spoczywająca na sztywnym podłożu pod działaniem impulsu momentu skręcającego - Ghosh, S.Ch. (Engineering Transactions, 1969)
A stiff circular disk is attached to the surface of a thick elastic plate resting on a rigid foundation..A twisting moment is Pδ (t)/r applied to the disk, where P is a constant and δ(t) denotes the Dirac function. Employing the Cagniard and Dix method, the displacement of a disk arbitrary point has been determined which is produced by successive reflections of the arised waves against the semiinfinite medium and the plate bottom surface, z = h.